Can a Stent Retriever Damage the JET 7 Reperfusion Catheter? - Pearly Ti, J.; Yeo, L.; Anil, G. (American Journal of Neuroradiology, 2020)
SUMMARY: We encountered 2 separate instances of damage to JET 7 reperfusion catheters when they were used in conjunction with a stent retriever during mechanical thrombectomy. On both occasions, after 1 or 2 passes with a stent retriever, we found that the distal end of the catheter was frayed and it ballooned up on flushing with saline. This mechanical failure could potentially lead to serious complications; hence, it should be shared with fellow neurointerventionalists.DACdistal access catheters